Implementation of Waqf for Cooperative Economic Development: Case Study of Primkop Kartika Ardagusema Cooperative - Salafuddin, Arif; Hoerudin, Cecep Wahyu; Wahyudinata, Yusuf Ramdhan (Yayasan Azka Hafidz Maulana, 2025)
This study aims to analyze the implementation of waqf as an instrument to improve the economic development of cooperatives, focusing on the Primkop Kartika Ardagusema Cooperative. This cooperative implements waqf to fund various economic empowerment programs that support the welfare of its members. This study uses a qualitative approach with a case study method, involving interviews with cooperative administrators and secondary data analysis. The results of the study indicate that waqf can be an effective tool to support the development of cooperative businesses and provide sustainable economic benefits for members. However, there are challenges in the management of productive waqf that need to be overcome to maximize the potential of waqf in cooperatives. This study provides recommendations for more transparent and efficient waqf management